PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TWO STAY TWO STRAY (TSTS) UNTUK MENINGKAT HASIL BELAJAR IPS SISWA KELAS IV SDN 8 BENGKALIS - ', Elpina; ', Lazim N; Noviana, Eddy (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The problem of this research is the weakness of student’s learning result of social subject. It show from 32 students, 20 students (62,50%) have lower score, and it is only 12 students (37,50%) have average score 67,6. The KKM of this school is 70. According to that problem, the research by implementing cooperative learning model two stay two stray (tsts). In cycle 1, the percentage of teachers activity in first meeting is adquate 66,6%. In second meeting, teachers activity significantly increased to 79,1% with good category. In cycle 2, first meeting was in good category 83,3% and second meeting indicated a very good category 95,8%. Meanwhile, the activity of students also improved. In cycle 1 indicated 62,5% in adequatee category and in cycle 2 has increased up to 83,3% with good category. In cycle 2, first meeting, the meeting, the activity of students has been increasing to 91,8%. With very good category and second meeting indicated very good category 95,8%. In concloussion, implemantation cooperative learning model two stay to stray (tsts) improve students learning result of fourth grade students of SD N8 bengkalis in social subject. Key words: Cooperative medel two stay two stray, learning result of social subject